2019
DOI: 10.22146/gamaijb.39647
|View full text |Cite
|
Sign up to set email alerts
|

Linking supervisor incivility with job embeddedness and cynicism: The mediating role of employee self-efficacy

Abstract: Applying the conservation of resource resources theory and the self-efficacy theory, this study investigates the relationship between supervisor incivility, self-efficacy, cynicism and the job embeddedness of employees in the hotel industry. The role of self-efficacy, as an important variable that mediates the relationship between the predictor and the criterion variable, is significantly evaluated. A non-probability sampling technique was used to collect 245 questionnaires from frontline employees of five and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…For instance, workplace incivility has been documented to relates negatively to organizational citizenship behavior ( Liu and Zhou, 2018 ), job satisfaction ( Koon, 2017 ; Alola et al, 2018 ), intention to stay ( Griffin, 2010 ), and employee performance ( Chen et al, 2013 ). Additionally, studies have confirmed that incivility prompts behavioral strains that lead to adversarial effects like workplace deviance ( Penney and Spector, 2005 ), intentional withdrawal ( Sliter et al, 2012 ), turnover intentions ( Huang and Lin, 2019 ), and increased employee cynical behaviors ( Alola et al, 2019a ). To better understand its antecedents and outcomes, it is necessary to differentiate individuals based on personality attributes that initiate patterns of uncivil conducts at the workplace and to explore potential ways to reduce its negative impacts.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, workplace incivility has been documented to relates negatively to organizational citizenship behavior ( Liu and Zhou, 2018 ), job satisfaction ( Koon, 2017 ; Alola et al, 2018 ), intention to stay ( Griffin, 2010 ), and employee performance ( Chen et al, 2013 ). Additionally, studies have confirmed that incivility prompts behavioral strains that lead to adversarial effects like workplace deviance ( Penney and Spector, 2005 ), intentional withdrawal ( Sliter et al, 2012 ), turnover intentions ( Huang and Lin, 2019 ), and increased employee cynical behaviors ( Alola et al, 2019a ). To better understand its antecedents and outcomes, it is necessary to differentiate individuals based on personality attributes that initiate patterns of uncivil conducts at the workplace and to explore potential ways to reduce its negative impacts.…”
Section: Introductionmentioning
confidence: 99%
“…For the three variables, all the loadings loaded in their right proportion ranging from .896 to .505. The model fit statistics ( x 2 = 241.88, df = 62, CFI = .950, GFI = .943, AGFI = .916, IFI = .961, SRMR = 0.13, RMSEA = 0.06) shows a good fit (Alola, Asongu, & Alola, 2019; Alola, Avci, & Ozturen, 2018). In addition, for the composite reliability (CR) and the average variance extracted (AVE) were all observed.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Further, school leaders should promote effective safety management and improve employees' engagement through fair policies and formal organizational structures. A positive, safe atmosphere in the workplace, with high-quality and cooperative relationships (Alola et al. , 2019) can eliminate SI.…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal offenses and inappropriate behavior may be expressed by students, parents, colleagues or superiors (Sulea et al, 2012). Supervisor behaviors in particular may be perceived as abusive and manipulative to most teachers, because of the power and authority they have over their subordinates (Cortina et al, 2001;Alola et al, 2019), thus affecting the degree of closeness they develop with them and exerting a negative effect on teachers' professional life.…”
Section: Introductionmentioning
confidence: 99%